Outcome of Surgery for Primary Hyperparathyroidism (Bangladesh Journal of Otorhinolaryngology, 2025)
Background: A common endocrine condition with a range of clinical manifestations and outcomes is primary hyperparathyroidism. The purpose of this study was to assess the surgical results for primary hyperparathyroidism.Aim of the study: The Aim of the study is to assess the outcome of surgery for primary hyperparathyroidism.Methods: A prospective observational study was conducted in the Head and Neck Surgery Division of the Department of Otolaryngology-Head & Neck Surgery, BSMMU, Shahbag, Dhaka from August 2022 to January 2023. 35 patients underwent parathyroidectomy. The data was collected and analyzed using SPSS 26.0 (Statistical Package for the Social Science). The statistical significance was set to p